2014
DOI: 10.1080/13554794.2014.962548
|View full text |Cite
|
Sign up to set email alerts
|

Visual hallucinations of autobiographic memory and asomatognosia: a case of epilepsy due to brain cysticercosis

Abstract: The current study describes the case of a woman with symptomatic epilepsy due to brain cysticercosis acquired during childhood. During her adolescence, she developed seizures characterized by metamorphopsia, hallucinations of autobiographic memory and, finally, asomatognosia. Magnetic brain imaging showed a calcified lesion in the right occipitotemporal cortex, and positron emission tomography imaging confirmed the presence of interictal hypometabolism in two regions: the right parietal cortex and the right la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…32,33 While this is theoretically possible – and must indeed occur in a reduced percentage of cases – several pieces of evidence favor a causal relationship between NCC and recurrent nonprovoked seizures. Published evidence include abundant descriptions of cases with focal epilepsies related to the location of a single parasite in the brain parenchyma, 3438 the higher prevalence of epilepsy in cysticercosis-endemic areas when compared with non-endemic regions, 39 and the occurrence of inflammatory changes surrounding parenchymal brain cysticerci immediately after a seizure in up to 50% cases. 40 In addition, while it has been suggested that some degenerating cysticerci may induce reactive seizures due to transient episodes of inflammation, calcified cysticerci – as those found in the present series – represent enduring epileptogenic lesions due to the gliosis that develops around dead parasites, as well as late exposure of residual antigenic material to the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 While this is theoretically possible – and must indeed occur in a reduced percentage of cases – several pieces of evidence favor a causal relationship between NCC and recurrent nonprovoked seizures. Published evidence include abundant descriptions of cases with focal epilepsies related to the location of a single parasite in the brain parenchyma, 3438 the higher prevalence of epilepsy in cysticercosis-endemic areas when compared with non-endemic regions, 39 and the occurrence of inflammatory changes surrounding parenchymal brain cysticerci immediately after a seizure in up to 50% cases. 40 In addition, while it has been suggested that some degenerating cysticerci may induce reactive seizures due to transient episodes of inflammation, calcified cysticerci – as those found in the present series – represent enduring epileptogenic lesions due to the gliosis that develops around dead parasites, as well as late exposure of residual antigenic material to the brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%